Exploring the associations between student participation, wellbeing and recognition at school. Issue 4 (4th July 2022) - Graham, Anne; Anderson, Donnah; Truscott, Julia; Simmons, Catharine; Thomas, Nigel Patrick; Cashmore, Judy; Bessell, Sharon
ABSTRACT: Children's right to participate, at least in rhetoric, is well recognised, but what this means and the associated benefits in schools are less clear. This article synthesises findings of a large mixed-methods Australian study comprising policy analysis, qualitative interviews with students, teachers and policymakers, and the development of a Student Participation Scale, which was then used in a student survey to explore associations between participation and wellbeing. The study found that particular elements of participation (choice, influence and working together – but not 'voice') were strongly associated with greater wellbeing, both as a direct link and one mediated by intersubjective 'recognition' (relationships founded on reciprocal respect, valuing and care of others). The findings have considerable implications for both policy and practice in clarifying how participation is understood, practised and progressed in different 'spaces' in schools, as well as identifying the cultural conditions necessary for simultaneously fostering both participation and wellbeing.